Defense Industry Venture Financing: US Experience in the Ukrainian Dimension - Begma , Vitaly; Shemaev , Vladimir; Radov , Denis; Tolok , Polina (Social Development and Security, 2021)
The article analyzes the US experience in the use of venture capital in financing the development of modern models of weapons and military equipment and military and dual-use technologies. Studies of the efficiency of the use of venture capital in the United States have confirmed a positive correlation between venture capital and innovation in firms that use it. At the same time, there is a high level of patent activity, as well as large investments in research and development, which these firms do compared to other companies. The essence, features and influence of venture investments on the innovative development of the defense industry, its contribution to the economic development of the country as a whole are revealed. The main advantages of using venture capital for the benefit of the US military are as follows: venture capital allows the use of non-military resources; return on investment is ensured and the army can earn a return on investment as their commercial market grows; venture capital helps to lift entire industries. Highlights the main challenges and trends of venture capital investment in the United States: Development of cooperation between military research units and developers of commercial technologies, government procurement rules, inflexible requirements for supervision and concerns about intellectual property. Possible promising areas for effective use of venture capital for the defense industry of Ukraine have been identified. To do this, it is necessary to create a new system of financial, credit and investment support for the defense industry, as well as to create a favorable investment climate for investment in the defense industry, in particular, a mechanism to protect these investments.